2013
DOI: 10.1155/2013/109367
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Photosynthesis, Fatty Acid Composition, ATPase and Acid Phosphatase Activities, and Anatomical Structure of Two Tea (Camellia sinensis (L.) O. Kuntze) Cultivars in Response to Fluoride

Abstract: The changes of photosynthetic parameters, water use efficiency (WUE), fatty acid composition, chlorophyll (Chl) content, malondialdehyde (MDA) content, ATPase and acid phosphatase activities, fluoride (F) content, and leaf anatomical structure of two tea cultivars, “Pingyangtezao” (PY) and “Fudingdabai” (FD), after F treatments were investigated. The results show that net photosynthetic rate (P n), stomatal conductance (g s), and transpiration rate (E) significantly decreased in both cultivars after 0.3 mM F t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The young leaves, stems, and roots of the seedlings were collected after 1 day of treatment at 0 and 0.3 mM NaF for expression analysis and after 14 days of treatment for fluoride measurement. The different tendency to fluoride accumulation in the four tea cultivars under the condition is consistent with the previous studies, as indicated in Table S1 …”
Section: Materials and Methodssupporting
confidence: 91%
See 4 more Smart Citations
“…The young leaves, stems, and roots of the seedlings were collected after 1 day of treatment at 0 and 0.3 mM NaF for expression analysis and after 14 days of treatment for fluoride measurement. The different tendency to fluoride accumulation in the four tea cultivars under the condition is consistent with the previous studies, as indicated in Table S1 …”
Section: Materials and Methodssupporting
confidence: 91%
“…The different tendency to fluoride accumulation in the four tea cultivars under the condition is consistent with the previous studies, as indicated in Table S1. 27 Cloning of the CsFEX Gene. Putative CsFEX ORF (CSA014827) was amplified with PrimeSTAR Max DNA polymerase (TAKARA) from cDNA extracted from leaves of Yunkang 10 and then cloned into the T Blunt vector.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations